Manajemen pada Pasien Sindroma Guillain-Barré Di ICU RSUP Dr. Sardjito - Jufan, Akhmad Yun; Sudadi; Sunantara, I Gusti Ngurah Putu Mandela (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Guillain-Barré syndrome (GBS) is an autoimmune disorder that affects the peripheral nervous system. Most patients with GBS are clinically characterized by tetraplegia with or without sensory disturbances. In GBS this is due to a hyperreactive immune response including release of antiganglioside antibodies, formation of antibody-dependent immune complexes, and increased macrophages leading to axonal demyelination and degeneration. Severe cases of GBS may present with progressive clinical signs involving respiratory muscle and requiring mechanical ventilation and treatment in an intensive care unit (ICU). We reported a 26-year-old woman with type 2 respiratory failure with suspicion of GBS who was being treated in the ICU of RSUP Dr. Sardjito and undergone plasma exchange as immunomodulator therapy. The patient was treated for 9 days in the ICU of RSUP Dr. Sardjito with the outcome of the patient discharged from ICU to the ward.